Irrigation service fees. Proceedings of the Regional Seminar on Irrigation Service Fees, Manila, Philippines, 21-25 July 1986 - Asian Development Bank; International Irrigation Management Institute (Asian Development Bank, 1986)
The book is a compilation of the proceedings and conclusions of the Regional Seminar on Irrigation Service Fees held in Manila, 21-25 July 1986, and includes a summary of the country papers presented at the Seminar.